Report on the Study of Impact of Plan Programmes in West Bengal Part-III Vol II - Planning Commission (Planning Commission, 1964)
The enquiry into the extent of utilisation of irrigation facilities and potential in West Bengal was taken up by the State Statistical Bureau in 1964-65 as an item of work of the study of the impact of plan programmes on levels of living, employment etc. , initiated by the Programme Evaluation Organisation, Planning Commission, Government of India. The present report is devoted to a study of the results obtained from this enquiry.
Government of West Bengal, State Statistical Bureau